Pengaruh Kerjasama Tim, Komunikasi dan Disiplin Kerja terhadap Kinerja Karyawan PT. Citra Mandala Surya Perkasa - Alfian, Alfian; Ayuni, Citra (Lembaga Yasin AlSys, 2025)
Employee performance is one of the important factors in achieving company goals; however, it is often influenced by a lack of teamwork, communication, and work discipline. This study aims to analyze the effect of teamwork, communication, and work discipline on employee performance at PT. Citra Mandala Surya Perkasa. The research method used is associative quantitative with data collection techniques through questionnaires distributed to 65 respondents who are employees of the company. The data analysis technique employs multiple linear regression with the assistance of SPSS 25. The results indicate that, partially, teamwork, communication, and work discipline have a significant effect on employee performance. Simultaneously, all three independent variables also show a significant effect on employee performance. These findings emphasize that improving the quality of teamwork, effective communication, and high work discipline can enhance overall employee performance. Therefore, the company management is advised to strengthen these aspects to achieve optimal productivity.